A comprehensive study on evolution and advancement of DC–DC cascaded converters: a review. Issue 1 (2nd January 2022) - Kumari, Rubi; Pandit, Moumi; Sherpa, K.S.
ABSTRACT: This paper investigates about the various topologies that can be utilised for meeting the global increasing demand that are not full-filled by conventional DC–DC converters. To meet the desired rise, different DC–DC cascaded converters are reviewed in this review paper, which are very much suitable for the renewable energy system. The modification of these DC–DC converters in terms of voltage boosting, power requirement, cost, circuit complexity and efficiency are comprehensively reviewed. Also, the applications of these cascaded converters in the field of renewable energy along with its advantage and disadvantages has been discussed in this paper.